Pengaruh Infrastruktur Telekomunikasi Dan Jalan Terhadap Pencapaian Tujuan Pembangunan Berkelanjutan Di Indonesia - zakia Nabila; Joan Marta (Universitas Negeri Padang, 2026)
This study aims to analyzes the influence of telecommunication and road infrastructure on poverty (SDG 1), unemployment (SDG 8), and income inequality (SDG 10) in Indonesia. Panel data for the 34 provinces for the 2019–2023 period was used using the panel data regression method, the Fixed Effect Model approach, and partial (t-test) and simultaneous (F-test) testing. Control variables include GDP per capita, human capital, and population density. The results show that telecommunication infrastructure has a negative and significant effect on poverty, unemployment, and income inequality. These findings confirm that increasing digital connectivity is able to improve welfare through access to information, business opportunities, and economic participation. On the other hand, road infrastructure did not have a significant influence on the three indicators. Simultaneously, telecommunications and roads have a significant influence, with the dominant contribution coming from telecommunications. In conclusion, digital connectivity-based development has a stronger role in supporting the achievement of the SDGs than road infrastructure development in the research period.